Effect of Lactobacillus delbrueckii on cholesterol metabolism in germ-free mice and on atherogenesis in apolipoprotein E knock-out mice - Portugal,L.R. (2006)
Elevated blood cholesterol is an important risk factor associated with atherosclerosis and coronary heart disease. Several studies have reported a decrease in serum cholesterol during the consumption of large doses of fermented dairy products or lactobacillus strains. The proposed mechanism for this effect is the removal or assimilation of intestinal cholesterol by the bacteria, reducing cholesterol absorption. Although this effect was demonstrated in vitro, its relevance in vivo is still controversial. Furthermore, few studies have investigated the role of lactobacilli in atherogenesis. The aim of the present study was to determine the effect of Lactobacillus delbrueckii on cholesterol metabolism in germ-free mice and the possible hypocholesterolemic and antiatherogenic action of these bacteria using atherosclerosis-prone apolipoprotein E (apo E) knock-out (KO) mice. For this purpose, Swiss/NIH germ-free mice were monoassociated with L. delbrueckii and fed a hypercholesterolemic diet for four weeks. In addition, apo E KO mice were fed a normal chow diet and treated with L. delbrueckii for 6 weeks. There was a reduction in cholesterol excretion in germ-free mice, which was not associated with changes in blood or liver cholesterol concentration. In apo E KO mice, no effect of L. delbrueckii was detected in blood, liver or fecal cholesterol. The atherosclerotic lesion in the aorta was also similar in mice receiving or not these bacteria. In conclusion, these results suggest that, although L. delbrueckii treatment was able to reduce cholesterol excretion in germ-free mice, no hypocholesterolemic or antiatherogenic effect was observed in apo E KO mice.